1999
DOI: 10.1073/pnas.96.24.13603
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinases of Caenorhabditis elegans : A model for signal transduction in multicellular organisms

Abstract: Caenorhabditis elegans should soon be the first multicellular organism whose complete genomic sequence has been determined. This achievement provides a unique opportunity for a comprehensive assessment of the signal transduction molecules required for the existence of a multicellular animal. Although the worm C. elegans may not much resemble humans, the molecules that regulate signal transduction in these two organisms prove to be quite similar. We focus here on the content and diversity of protein kinases pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
205
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(211 citation statements)
references
References 36 publications
3
205
1
2
Order By: Relevance
“…Previous studies demonstrated that TAK1 plays important roles in immunological and developmental contexts across many species (Plowman et al, 1999;Sakaguchi et al, 2004;Wan et al, 2006;Delaney et al, 2006;Kajino et al, 2008). In mammalian tissues, TAK1 is essential for responses to a variety of inflammatory ligands, it can involve in p38 activation by MKK3/6 or in JNK activation by MKK4/7 (Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that TAK1 plays important roles in immunological and developmental contexts across many species (Plowman et al, 1999;Sakaguchi et al, 2004;Wan et al, 2006;Delaney et al, 2006;Kajino et al, 2008). In mammalian tissues, TAK1 is essential for responses to a variety of inflammatory ligands, it can involve in p38 activation by MKK3/6 or in JNK activation by MKK4/7 (Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The RLK/Pelle family is defined as the clade that contains RLK/Pelle representative sequences and forms sister group relationships to Raf kinases and receptor tyrosine kinases. The other kinase families were defined based on the kinase classification schemes for budding yeast (Hunter and Plowman, 1997), worm (Plowman et al, 1999), and human kinases (Manning et al, 2002). Two to three representative sequences from each kinase family in each organism were chosen to generate alignments with Arabidopsis or rice kinases.…”
Section: Alignments and Phylogenetic Reconstructionmentioning
confidence: 99%
“…The Arabidopsis genome encodes 1,085 typical protein kinases (M. Gribskov, unpublished data), which is about 4% of the predicted 25,500 genes (Arabidopsis Genome Initiative, 2000). Not only is the proportion of Arabidopsis kinase genes about twice that found in Brewer's yeast (Saccharomyces cerevisiae; Hunter and Plowman, 1997) or Caenorhabditis elegans (Plowman et al, 1999), but there are also major differences in the types of kinases found in plants. For example, receptor kinases in plants phosphorylate Ser and Thr residues, whereas in animals, the predominant type of receptor kinase phosphorylates Tyr residues.…”
mentioning
confidence: 99%